(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical activity on prescription (FaR) is a structured, evidence-based intervention aimed at increasing physical activity among patients through individualised prescriptions provided by healthcare professionals. With support from approximately 60 scientific publications and inclusion in Sweden’s 2024 national guidelines for unhealthy lifestyle habits, FaR is a recommended tool in health care. Several strategies have been tested to implement FaR in Region Stockholm’s primary care system, including staff training and support materials. However, uptake remains inconsistent across services, leading to unequal care. The aim of this project was to develop and implement a new, scalable model to integrate FaR as a routine component of primary care practice. Project Description: To develop the implementation model, a comprehensive approach was undertaken to integrate FaR as a routine component of primary care practice. The model is based on previously identified, evidence-informed implementation strategies and is designed to support long-term sustainability. The innovation lies in combining multiple evidence-informed implementation strategies in a practical, real-world context. Key components include: • A digital e-learning course • Development of local routines • Ongoing education and supervision • Structured follow-up using electronic health records • Implementation support via a digital platform The model is being tested in Region Stockholm through a project (2023–2025) involving 50–75 primary healthcare units annually. Evaluation includes: • Number of FaR prescriptions, measured at baseline, 3- and 6-months post-intervention • Interviews with unit managers to explore perception of the implementation model • Questionnaires to assess staff experience Preliminary results show increased use of FaR and high acceptability among staff. Many report that the model is easy to apply and fits well into routine care. Dissemination efforts aim to scale up the model at both regional and national levels. Conclusion: This implementation model shows promise as a feasible and scalable approach for integrating FaR into primary care. It contributes to improved clinical routines and supports healthcare professionals in promoting physical activity among patients. By strengthening the use of FaR, the model may lead to improved population health and offers a replicable framework for other regions or countries aiming to implement evidence-based physical activity interventions in healthcare.